Neonatal alloimmune thrombocytopenia complicated with piperacillin drug antibody: a case report - MENG Zifan; ZHANG Shaoqiang; JU Qiang; LI Ying; YAN Songxia; WANG Haiyan (Zhongguo shuxue zazhi)
[Objective] To investigate the clinical symptoms, laboratory tests, and treatment strategies of a case of fetal/neonatal alloimmune thrombocytopenia (FNAIT) complicated with piperacillin drug antibody. [Methods] The platelet antibodies in the mother were screened and identified by ELISA. The HLA antigens of the newborn were genotyped through PCR-SSO, while the specificity of HLA antibodies in the mother was determined using a Single Antigen kit. The drug antibody was detected by a piperacillin kit. [Results] Maternal antibodies against paternally-derived platelet antigens were detected. The HLA genotypes of the newborn were identified as HLA A* 33∶03 and HLA B* 58∶01. The mother exhibited strong positive antibodies against the specific platelet antigens of the newborn, namely anti-HLA-A33 and anti-HLA-B58 antibodies. The piperacillin antibody was detected in the newborn. Following treatment of continuous intravenous immunoglobulin (IVIG), platelet transfusions, red blood cell transfusions and discontinuation of piperacillin treatment, the platelet count and hemoglobin levels increased in the newborn. [Conclusion] The newborn in this case was diagnosed with FNAIT complicated by the presence of anti-HLA-A33 and anti-HLA-B58 antibodies, as well as drug-induced hemolytic anemia caused by piperacillin drug antibody. The condition is more complicated under the influence of dual immune antibodies. Laboratory detection techniques such as platelet antibody and drug antibody tests can assist in early clinical diagnosis. At the same time, more active drug and blood transfusion treatments should be given in clinical practice to improve the prognosis.